2019
DOI: 10.3390/buildings9040101
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Retrofit of R/C T-Beams with Steel Fiber Polymers under Cyclic Loading Conditions

Abstract: This paper presents results of an experimental study on seismic response of reinforced concrete (RC) T-beams with shear deficiencies strengthened with externally bonded steel fiber reinforced polymer (SFRP) strips. Seven cantilever RC beams were strengthened with externally bonded uniaxial SFRP strips in a U-shape configuration and were tested under cyclic loading conditions. The two main variables examined were the strip spacing and the use of anchoring system. Among the investigated anchoring systems, one wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…The adopted limit state of the following scenarios focused on depicting the developed strains onto the CFRP layers. We chose the aforementioned limit state since it was well known from the literature [38] that the ultimate strain capacity of CFRP ranges between 1.2-1.5%. Furthermore, the adhesive between the CFRP layers and mortar was not investigated due to the fact that the CFRP sheets were wrapped around the pipe, resulting in a perfect attachment of the composite, eliminating a debonding failure mode.…”
Section: Results and Discussion: Potential Application Of Cfrp For Forest Road Pipesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adopted limit state of the following scenarios focused on depicting the developed strains onto the CFRP layers. We chose the aforementioned limit state since it was well known from the literature [38] that the ultimate strain capacity of CFRP ranges between 1.2-1.5%. Furthermore, the adhesive between the CFRP layers and mortar was not investigated due to the fact that the CFRP sheets were wrapped around the pipe, resulting in a perfect attachment of the composite, eliminating a debonding failure mode.…”
Section: Results and Discussion: Potential Application Of Cfrp For Forest Road Pipesmentioning
confidence: 99%
“…For all cases where the strengthened RC pipes were put to the test, it was shown that the exploitation of the composite material was less than 50%, resulting to increased structural stability for the pipe. well known from the literature [38] that the ultimate strain capacity of CFRP ranges between 1.2-1.5%. Furthermore, the adhesive between the CFRP layers and mortar was not investigated due to the fact that the CFRP sheets were wrapped around the pipe, resulting in a perfect attachment of the composite, eliminating a debonding failure mode.…”
Section: Results and Discussion: Potential Application Of Cfrp For Forest Road Pipesmentioning
confidence: 99%
“…The aforementioned literature review reveals that the majority of the conducted research is focused on the application of nonconventional jackets in strengthening methods of original RC structural members [17][18][19]21,22,24,[26][27][28][30][31][32][33][34]36,[38][39][40][41][42][43][44][45][48][49][50]56]. Significantly fewer studies investigate such jackets for the repair of preloaded and slightly damaged RC specimens [20,23,25,29,35,37,46,47,[51][52][53][54][55].…”
Section: Research Significancementioning
confidence: 99%
“…These reasons have led researchers to switch to new jacketing techniques with alternative materials such as steel [17][18][19], advanced materials such as fiber reinforced polymer (FRP) [20][21][22][23][24][25], textile reinforced concrete or mortar [26][27][28][29] and shape memory alloys [30][31][32], cement-based materials such as ferrocement [33][34][35][36], steel fibrous concrete or mortar [37][38][39][40], high-performance fiber reinforced concrete [41][42][43][44][45][46][47][48], self-compacting concrete (SCC) [49][50][51][52][53][54], and thin slightly reinforced flowable mortar [55,56]. Many of these jacketing techniques have been proved successful substitutes to common RC jacketing.…”
Section: Introductionmentioning
confidence: 99%
“…Available innovative materials and intervention techniques such as steel fiber systems or fiber reinforced polymers (FRPs) in the form of sheets, strips and ropes are widely used. Suitable diagnosis and retrofit of deficient members can improve their strength, delay further corrosion of the reinforcement as well as reduce deformations at the serviceability limit stage [5][6][7][8][9][10][11]17].…”
Section: Introductionmentioning
confidence: 99%